Multilayer Observations and Modeling of Thunderstorm‐Generated Gravity Waves Over the Midwestern United States. Issue 23 (6th December 2019) - Heale, C. J.; Snively, J. B.; Bhatt, A. N.; Hoffmann, L.; Stephan, C. C.; Kendall, E. A.
Abstract: We present multilayer observations and numerical simulations of gravity waves (GWs) generated by a series of Mesoscale Convective Systems over the midwestern United States. Strong semiconcentric GWs were observed and modeled, which couple from their tropospheric sources to the thermosphere, displaying strong nonlinearity indicated by instability, breaking, and formation of turbulent vortices. GWs in the stratosphere display a large range of horizontal scales from 34–400 km; however, the smaller wavelength waves break rapidly in the mesosphere and lower thermosphere. Larger‐scale (≥150 km) waves dominate in the thermosphere and display northwestward propagation at 200–300 km altitude, opposing the mean winds. Despite strong molecular viscosity and thermal conductivity in the thermosphere, steepened wave fronts, which may indicate nonlinearity, is identified in 630 nm airglow imagers. The agreement between model and data suggests new opportunities for data‐constrained simulations that span multilayer observables, including mesosphere and lower thermosphere‐region airglow not captured for this event. Key Points: Coherent gravity waves were observed above thunderstorms, in the stratosphere by AIRS and thermosphere by MANGO Simulations of waves generated by convective sources defined by radar data closely match the observations in scale Results indicate that gravity waves may evolve nonlinearly well into the thermosphere and ionosphere